The concept of logistics performance in international trade framework: An empirical evaluation of logistics performance index - Bilgin, Cevat (IGI Global, 2022)
An increased need for international logistics has emerged with a higher degree of globalization. The quality of logistics services determines the degree of a country's involvement in global trade. In this chapter, the concept of logistics performance in the international trade context is discussed, then the measurement problems of logistics performance are discussed. The links between logistics, trade, and growth are evaluated theoretically. Policymakers and researchers have been widely using Logistics Performance Index (LPI) developed by the World Bank. LPI provides a general information of logistics costs, customs processes, and the quality of the necessary infrastructure for transportation for each country. In this chapter, the definition, the methodology, and the aspects of the indicator LPI, its content and components, and the relations between LPI and some economic factors such as growth and foreign trade, are elaborated. The econometric modelling methods are used to analyze the relations between LPI and economic factors. © 2023 by IGI Global. All rights reserved.